Strengthening Cooperative Governance and Management Capacity Through Business Plan and Budget (RBA) Preparation and Digital Financial Analysis - Yusnaini; Arista Hakiki; Ika Sasti Ferina; Yuliana (PT. Altaf Publishing Corp, 2026)
This Community Service Program aims to strengthen the managerial capacity of the Employee Cooperative of PT. Pusri Palembang through training and mentoring in the preparation of a Business Plan and Budget (Rencana Bisnis dan Anggaran – RBA) based on financial statement analysis. This activity represents a continuation of community service programs conducted in Phases I–VI (2019–2024), which focused on strengthening the cooperative’s accounting information system and improving the interpretation of financial statements. The main problems faced by the cooperative include the absence of a comprehensive RBA, the suboptimal use of historical financial statements as a basis for planning, and limited formulation of targets and performance indicators for each business unit. Through intensive workshops, the development of a Digital Spreadsheet Analysis Template for RBA, and technical mentoring for all business units, the program succeeded in increasing participants’ understanding by 78%, based on post-test results. The program produced several strategic outputs, including the cooperative’s annual RBA document, an interactive RBA template integrated with the cooperative’s accounting information system, and a draft scientific publication. The mentoring activities demonstrate that cooperative managers are now able to independently prepare financial projections, set revenue and cost targets, conduct scenario analysis, and develop business plans for each operational unit. Furthermore, the program has encouraged the development of a data-driven decision-making culture and strengthened cooperative governance, enabling the cooperative to progress toward becoming a modern, professional, accountable, and sustainable business entity.